Pengaruh Firm Size, Leverage, Capital Expenditure, Profitability Dan Liquidity Terhadap Cash Holding - Zaputra, Nikky Laurent; Yanti, Yanti (Jurnal Paradigma Akuntansi, 2025)
This study aims to determine whether firm size, leverage, capital expenditure, profitability and liquidity have an influence on cash holdings in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic. The period in this study is from 2020 to 2022. The sample selection technique used in this study is a purposive sampling technique. The sample in this study were 50 companies with a total of 150 data analyzed using multiple linear regression analysis. Data processing uses Eviews 12 software and Microsoft Excel 2019. The results in this study are firm size, capital expenditure and profitability have no effect on cash holdings during the COVID-19 pandemic, while leverage and liquidity have a significant positive effect on cash holdings during the COVID-19 pandemic.